Design Strategies for a Sustainable Home Landscape - Gail Hansen de Chapman (EDIS)
ENH-1110, a 5-page fact sheet by Gail Hansen de Chapman, describes strategies for landscape design that is Florida-friendly without compromising aesthetics. Includes references. Published by the UF Department of Environmental Horticulture, January 2009.